2006
DOI: 10.1007/s00248-006-9066-4
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Analysis of Soil Yeasts Isolated from a Latitudinal Gradient

Abstract: Yeast isolates from soil samples collected from a latitudinal gradient (>77 degrees S to >64 degrees N) were subjected to multivariate analysis to produce a statistical foundation for observed relationships between habitat characteristics and the distribution of yeast taxa (at various systematic levels) in soil microbial communities. Combinations of temperature, rainfall (highly correlated with net primary productivity), and electrical conductivity (EC) could explain up to ca. 44% of the distribution of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 27 publications
6
86
1
2
Order By: Relevance
“…were also detected as the major fungal population in the soil of natural areas in some other studies too (Wuczkowski and Prillinger, 2004;Vishniac, 2006;Connell et al, 2008). The predominance of Cryptococcus species in soils has been attributed to the unique polysaccharide capsules surrounding those (McFadden et al, 2006) that aid in the assimilation of nutrients from soil and thus competing with bacteria and other fungi in arid soils (Vishniac, 2006). The functioning and stability of terrestrial ecosystems are determined by biodiversity and species composition (McCann, 2000).…”
Section: Discussionmentioning
confidence: 92%
“…were also detected as the major fungal population in the soil of natural areas in some other studies too (Wuczkowski and Prillinger, 2004;Vishniac, 2006;Connell et al, 2008). The predominance of Cryptococcus species in soils has been attributed to the unique polysaccharide capsules surrounding those (McFadden et al, 2006) that aid in the assimilation of nutrients from soil and thus competing with bacteria and other fungi in arid soils (Vishniac, 2006). The functioning and stability of terrestrial ecosystems are determined by biodiversity and species composition (McCann, 2000).…”
Section: Discussionmentioning
confidence: 92%
“…Our working model is that the reservoir is the high elevation volcanoes discussed in this paper, because that is where we find the highest relative abundance of members of this group (see next section) on a global scale. The relative abundance of Naganishia species in microbial communities of the Dry Valleys of Antarctica is less clear because most studies have been based on culture-dependent approaches focusing solely on specific species (Vishniac and Hempfling 1979; Vishniac 1985a, 1985b, 2006). Two recent culture-independent studies of microbial communities indicated that Naganishia are rare in many Dry Valley soils (Fell et al 2006), but are quite common in several higher elevation sites (Dreesens et al 2014).…”
Section: Global Aerial Dispersal Of Naganishia Speciesmentioning
confidence: 99%
“…Broader and more general discussions of the biogeography of yeasts found in cold environments are available in the literature (e.g. Vishniac 2006; Buzzini et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our understanding of the spatial distribution patterns of bacterial diversity is limited, mainly because most studies are limited to local scales (Navarro-Gonzalez et al, 2003;Zhou et al, 2004). Recent large-scale surveys have revealed that different ecosystems support unique microbial populations (Zhou et al, 2002;Fierer and Jackson, 2006;Green and Bohannan, 2006;Vishniac, 2006;Adler and Levine, 2007), giving rise to the notion that microbial populations can exhibit geographic distribution. These emerging microbial distribution patterns suggest that the ecological rules followed by macroorganisms do not necessarily apply to microorganisms (Fierer and Jackson, 2006;Green and Bohannan, 2006;Bryant et al, 2008).…”
Section: Introductionmentioning
confidence: 99%